Robust guaranteed-cost sliding control for brushless DC motors by LMI. (15th October 2012) - Soliman, Hisham M.; Bayoumi, Ehab H.E.; Soliman, Mostafa
Two state feedback sliding mode control schemes are developed for position control for brushless DC motor drives. The first controller design achieves the desired swiftness of response. In addition to swiftness, the second controller drastically reduces system's chattering by adding the guaranteed cost constraint. The proposed controller consists of two parts, linear and non-linear. Linear matrix inequalities (LMIs) optimisation is used to design the linear part that achieves the desired dynamic performance: it is robust against system uncertainties, and is based on a new sufficient condition for the existence problem; the non-linear part is created to guarantee that the sliding surface is attained. System uncertainty due to changes in drive's load inertia is represented with norm- bounded structure. The main advantages of this technique are that: the LMI algorithm includes an optimal part to preclude high control efforts, and the control burden is heavily placed on the linear part to improve the chattering problem of the conventional sliding mode control.